Adaptation to Aquatic Risks due to Climate Change in Pangnirtung, Nunavut - Giles, Audrey R.; Strachan, Shaelyn M.; Doucette, Michelle; Stadig, Gwenyth S.; Pangnirtung, The Municipality of (ARCTIC, 2013)
We use a vulnerability framework to examine how residents of Pangnirtung, Nunavut, perceive the risks of aquatic activities in the context of adaptation to a changing climate. Our findings suggest that community members identify climate change as increasing the risk of many aquatic activities and have adapted some practices accordingly. However, further adaptation to these changing risks is impeded by three main barriers: (1) financial constraints, (2) Inuit resistance to adopting what some consider Euro-Canadian water safety practices, and (3) issues with the design of flotation devices. Participants suggested the following practical changes: (1) make personal flotation devices, lifejackets, and floater suits available to all residents at local stores at a subsidized rate, or provide them free of charge through the community; (2) create water safety promotional items that feature locally developed messages in both Inuktitut and English; (3) include traditional knowledge in water safety campaigns; and (4) use the local pool to train residents in water safety. These changes would not only help residents adapt to changing risks, but also help incorporate climate considerations into policies and programs. Nous utilisons un cadre de vulnérabilité pour examiner comment les habitants de Pangnirtung, au Nunavut, perçoivent les risques inhérents aux activités aquatiques dans le contexte de l’adaptation au changement climatique. Cette étude nous a permis de constater que les membres de la collectivité estiment que le changement climatique augmente le risque de nombreuses activités aquatiques et qu’ils ont modifié certaines de leurs manières de faire en conséquence. Cependant, trois grands obstacles entravent une adaptation plus poussée de ces risques : 1) les contraintes financières, 2) la résistance des Inuits à adopter ce que certains considèrent comme des méthodes eurocanadiennes plus sécuritaires, et 3) des problèmes de conception des appareils de flottaison. Les participants ont suggéré les changements pratiques ...